Reduction of in-stent thrombus immediately after percutaneous coronary intervention by pretreatment with prasugrel compared with clopidogrel: An optical coherence tomography study. Issue 2 (February 2017) - Kubo, Takashi; Ino, Yasushi; Matsuo, Yoshiki; Shiono, Yasutsugu; Kameyama, Takeyoshi; Yamano, Takashi; Katayama, Yosuke; Taruya, Akira; Nishiguchi, Tsuyoshi; Satogami, Keisuke; Kashiyama, Kuninobu; Orii, Makoto; et al.
Abstract: Background: Prasugrel is a new-generation thienopyridine antiplatelet agent that provides more consistent and prompt platelet inhibition than clopidogrel. The aim of this study was to compare in-stent thrombus inhibition effect of pretreatment with prasugrel and clopidogrel by using optical coherence tomography (OCT) immediately after percutaneous coronary intervention (PCI) for acute coronary syndrome (ACS). Methods: We performed OCT immediately after PCI in 108 ACS patients pretreated with either prasugrel ( n  = 51) or clopidogrel ( n  = 57). OCT detected thrombus/plaque protrusion in all stented segments. Results: Although stent volume (190.4 ± 119.1 mm 3 vs. 189.4 ± 95.8 mm 3, p  = 0.961), mean stent area (6.9 ± 2.9 mm 2 vs. 7.1 ± 2.0 mm 2, p  = 0.772), and minimum stent area (5.6 ± 2.7 mm 2 vs. 5.4 ± 1.7 mm 2, p  = 0.554) were not different between the two groups, in-stent thrombus/plaque protrusion volume (1.8 ± 2.9 mm 3 vs. 4.5 ± 5.3 mm 3, p  = 0.002), mean in-stent thrombus/plaque protrusion area (0.1 ± 0.1 mm 2 vs. 0.2 ± 0.2 mm 2, p  = 0.005), and maximum in-stent thrombus/plaque protrusion area (0.5 ± 0.7 mm 2 vs. 0.8 ± 0.6 mm 2, p  = 0.007) were significantly smaller in the prasugrel group compared with the clopidogrel group. Conclusions: Pretreatment with prasugrel was associated with significantly reduced in-stent thrombus/plaque protrusion immediately after PCI for ACS compared with that with clopidogrel.